Moon Effect on Paciic Basin Stock Markets - Brahmana, Rayenda Khresna; Hooy, Chee Wooi; Ahmad, Zamri (The Indonesian Capital Market Review, 2011)
This is an empirical study on the inluences of moon on seven stock markets, which are Indonesia, Malaysia, United Kingdom, United States, Philippines, Japan, and Thailand. The period is from January 1999 until December 2009 in daily basis. This study investigates the relationship between moon phase and market returns. We divided moon phases into new moon and full moon. While literature mention the relationship between moon phase and market returns, our research reject the null hypothesis in regression analysis. However, the descriptive catches the indication and conirmed previous research. It also proposes that the market is still rational and not moon-mood inluenced. This result is not contending the EMH theorem. Further research is needed in term of investigating the relationship between psychology factors (heuristic bias, information ignorance, and other factors) and investor behavior. The effect of moon on certain anomalies has to examine speciically.